SUPERVISORS’ RATINGS OF COMPUTER SKILLS POSSESSED BY SECRETARIES FOR EFFECTIVE WORK PERFORMANCE IN COLLEGES OF EDUCATION IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study was undertaken to determine supervisors’ ratings of the extent computerskills are possessed by secretaries for effective work performance in colleges ofeducation in Delta State. The study adopted the survey research design and wasguided by four research questions while four null hypotheses were tested at 0.05 levelofsignificance. The entire population of 132 supervisors (deans, heads of departmentsand directors of programmmes) in the four colleges of education in Delta State wasused for the study. A 40 item structured questionnaire with five response options wasused for data collection. The questionnaire was validated by three experts and itsreliability co-efficient of 0.86 was calculated using Pearson Product MomentCorrelation. Data relating to the research questions were analyzed using mean andstandard deviation while analysis of variance (ANOVA) was used to test the four nullhypotheses. The study found that secretaries in colleges of education in Delta Statepossessed word processing skills, electronic spreadsheet skills, internet applicationskills and power-point presentation skills at a moderate extent. Respondents’ meanratings were not significantly influenced by their qualifications and designations.Based on the findings, it was concluded that the moderate possession of computerskills by secretaries in colleges of education in Delta State may be affecting theireffective performances in the present technology driven era. It was recommendedamong others that authorities of colleges of education in Delta State should regularlyorganize retraining programmes for secretaries on the usage of computer and its applications.
Keywords: Internet, Secretaries, Skills, Spreadsheet, Power-Point, Word-Processing